2011
DOI: 10.1007/s10311-011-0336-0
|View full text |Cite
|
Sign up to set email alerts
|

Lichens to distinguish urban from industrial PAHs

Abstract: This paper shows that lichens can be used as biomonitors to distinguish urban from industrial polycyclic aromatic hydrocarbons (PAHs). PAHs are atmospheric pollutants originating mainly from incomplete combustion of fuels in vehicles and industry. The occurrence of PAHs in air is a serious health issue in urban areas and industrial areas because some PAHs are carcinogenic. Biomonitoring PAHs with lichens is generally applied for quantification of PAHs. However, the precise sources of PAHs are not well known. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…It has been observed in Rudraprayag area of the region that organic pollutants (based on semivolatile properties) as well as inorganic pollutants (based of density of the metal) has a tendency to move with the moving air mass and the direction of the wind (Shukla et al 2013;Shukla et al 2014) Lichen biomonitoring data has confirmed that among the different ringed PAHs, 4 ringed PAHs depending on their semivolatile nature tend to associate with the suspended particulate matter and travel long distance from its source of origin (Shukla et al 2013). In an effort to observe source apportionment of PAHs, the PAH ratio calculation based on biomonitoring data clearly distinguished between emissions from petrol driven vehicles and diesel driven vehicles, indicating that diesel driven vehicles (due to tourist activity) are major source of PAH pollution in Garhwal Himalayas (Shukla et al 2012). Studies demonstrated that narrow valleys provide unidirectional movement of pollutants/emissions towards higher altitude causing temperature rise in the area because of increase in concentration of aerosols and greenhouse gases.…”
Section: Lichen Biomonitoring Data For Validationmentioning
confidence: 83%
“…It has been observed in Rudraprayag area of the region that organic pollutants (based on semivolatile properties) as well as inorganic pollutants (based of density of the metal) has a tendency to move with the moving air mass and the direction of the wind (Shukla et al 2013;Shukla et al 2014) Lichen biomonitoring data has confirmed that among the different ringed PAHs, 4 ringed PAHs depending on their semivolatile nature tend to associate with the suspended particulate matter and travel long distance from its source of origin (Shukla et al 2013). In an effort to observe source apportionment of PAHs, the PAH ratio calculation based on biomonitoring data clearly distinguished between emissions from petrol driven vehicles and diesel driven vehicles, indicating that diesel driven vehicles (due to tourist activity) are major source of PAH pollution in Garhwal Himalayas (Shukla et al 2012). Studies demonstrated that narrow valleys provide unidirectional movement of pollutants/emissions towards higher altitude causing temperature rise in the area because of increase in concentration of aerosols and greenhouse gases.…”
Section: Lichen Biomonitoring Data For Validationmentioning
confidence: 83%
“…Pyxine subcinerea Stirton (Fig. 4.8b ) Description : A foliose lobate pseudocyphellate thallus of 7 cm across with 1-2 mmwide lobes; upper side greyish; margins intermittently pseudocyphellate; pseudocyphallae developing into soralia and Upreti 2007a , b , c , 2009 ;Shukla et al 2010Shukla et al , 2011Shukla et al , 2012aRani et al 2011 Habitat : Saxicolous Distribution : The species grow frequently on rocks or on soil over rocks near glacier and exposed areas in alpine and higher temperate areas. Indicator value : Intermediate; PAHs (Shukla et al 2010 ) 15.…”
Section: Bioindicator Lichen Speciesmentioning
confidence: 99%
“…Other inherent abiotic aspects from nature including sunlight, wind, soil, water, climate form a complex self-reorganization behavior in presence of society. This might also include the danger of environmental pollution arising from human and more industrial activities (Espíndola-Gonzalez et al, 2010;Shukla et al, 2012;Wang et al, 2006;Srogi, 2007). Computer modelling on specific data also shapes the future of urban design (Jeon et al, 2008).…”
Section: Environmental Chemistry -Urban Chemistrymentioning
confidence: 99%